2009
DOI: 10.1172/jci38714
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell entrapment within the pregnant uterus inhibits immune surveillance of the maternal/fetal interface in mice

Abstract: Embryo implantation induces formation of the decidua, a stromal cell-derived structure that encases the fetus and placenta. Using the mouse as a model organism, we have found that this tissue reaction prevents DCs stationed at the maternal/fetal interface from migrating to the lymphatic vessels of the uterus and thus reaching the draining lymph nodes. Strikingly, decidual DCs remained immobile even after being stimulated with LPS and exhibiting responsiveness to CCL21, the chemokine that drives DC entry into l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(223 citation statements)
references
References 48 publications
(53 reference statements)
7
203
2
2
Order By: Relevance
“…In murine models of pregnancy, a phenomenon known as 'DC entrapment' has been reported, where decidual DCs fail to migrate to uterine lymph nodes following their activation (Collins et al 2009). It has been postulated that this may serve to limit adaptive T cell responsiveness towards fetal/placental antigens and restrict immunosurveillance specifically at the maternal-fetal interface.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…In murine models of pregnancy, a phenomenon known as 'DC entrapment' has been reported, where decidual DCs fail to migrate to uterine lymph nodes following their activation (Collins et al 2009). It has been postulated that this may serve to limit adaptive T cell responsiveness towards fetal/placental antigens and restrict immunosurveillance specifically at the maternal-fetal interface.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Pregnancy induces changes in lymphoid organs, inducing, for example, thymic depletion 53,54 and blockade of dendritic cell movement to uterine-draining lymph nodes. 55 Several investigators suggest that in women, as in mice, uNK cell progenitors are of mixed endometrial and peripheral origins.…”
Section: Human Unk Cells and Their Functionsmentioning
confidence: 99%
“…Extensive literature documents the presence of immune cells at the maternal-fetal interface. [13][14][15][16][17][18][19] However, it is not entirely clear how these immune cells are recruited or their pregnancy specific functions. Studies over the past few decades have suggested the presence of progenitor stem cells in the uterus that differentiate during early pregnancy 20 and/or that immune cells are recruited from the peripheral blood by conceptus-dependent or -independent signals.…”
Section: Introductionmentioning
confidence: 99%